Pogostemon jaitapurensis (Lamiaceae), a new species from India based on morphological and molecular evidence - Chandore, Arun Nivrutti; Tamboli, Asif Shabodin; Borude, Devidas Bhausaheb; Gholave, Avinash Ramchandra; Govindwar, Sanjay Prabhu; Yadav, Shrirang Ramachandra (Phytotaxa, 2021)
Based on morphological and molecular analyses, Pogostemon jaitapurensis is described and illustrated as a new species from Konkan region of Maharashtra, India. Present study added the molecular data of Indian endemic Pogostemon species of sect. Verticillatus and provide their phylogenetic placement. The bayesian and parsimony phylogenetic analyses conducted resolve Pogostemon into two clades, from them the new species belongs to Clade B and shows close relationship with species of sect. Verticillatus. A possible relationship between the new species and P. deccanensis and P. erectus, endemic to India, is also revealed by the phylogenetic analyses. Phylogenetically, the new species has been also placed in genus Pogostemon subg. Dysophyllus sect. Verticillatus. Sectional classification of these species is congruent with their phylogenetic positions.